2017
DOI: 10.1155/2017/4846876
|View full text |Cite
|
Sign up to set email alerts
|

Qingchang Wenzhong Decoction Attenuates DSS‐Induced Colitis in Rats by Reducing Inflammation and Improving Intestinal Barrier Function via Upregulating the MSP/RON Signalling Pathway

Abstract: Ulcerative colitis (UC) is a chronic, nonspecific, inflammatory disease for which an effective treatment is lacking. Our previous study found that Qingchang Wenzhong Decoction (QCWZD) can significantly improve the clinical symptoms of UC and ameliorate dextran sulphate sodium- (DSS-) induced ulcerative colitis in rats by downregulating the IP10/CXCR3 axis–mediated inflammatory response. The purpose of the present study was to further explore the mechanism of QCWZD for UC in rats models, which were established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Because QCWZD is a compound of multiflavor Chinese medicines and each of them has different chemical constituents, it may have regulatory effects on UC through multilinks and multiple targets, so we carried out a number of studies. We found QCWZD can alleviate inflammatory reaction and improve the intestinal barrier function in DSS-induced UC rats by downregulating the IP10/CXCR3 axis [8] and upregulating the MSP/RON pathway [7]. Furthermore, we also found that QCWZD could resist the interactive network of inflammation, oxidative stress, apoptosis, and their overactivated interactions [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because QCWZD is a compound of multiflavor Chinese medicines and each of them has different chemical constituents, it may have regulatory effects on UC through multilinks and multiple targets, so we carried out a number of studies. We found QCWZD can alleviate inflammatory reaction and improve the intestinal barrier function in DSS-induced UC rats by downregulating the IP10/CXCR3 axis [8] and upregulating the MSP/RON pathway [7]. Furthermore, we also found that QCWZD could resist the interactive network of inflammation, oxidative stress, apoptosis, and their overactivated interactions [29].…”
Section: Discussionmentioning
confidence: 99%
“…Qingchang Wenzhong Decoction (QCWZD) is a potent traditional Chinese herbal formulation formulated by Junxiang Li. Our previous studies found that QCWZD could relieve the clinical symptoms of UC patients [5, 6], reduce inflammation, and improve the intestinal barrier function in dextran sulphate sodium (DSS)-induced UC rats [7, 8]. Recently we found that there was a difference in the composition and abundance of gut microbiota in patients with UC and healthy people [9]; we wonder if QCWZD could treat UC by regulating gut microbiota, which is involved in the occurrence and development of UC [10].…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al [5] indicated that Shenzhu Capsule contained two herbal medicines (Renshen and Baizhu) and improved UC by altering TNF signalling pathway, Toll-like receptor signalling pathway and NF-kb signalling pathway. Qingchang Wenzhong Decoction comprising of eight kinds of herbs attenuated dextran sulphate sodium-(DSS-) induced UC in rats by upregulating macrophage-stimulating protein concentration/receptor tyrosine kinase signalling pathway [6]. In addition, Quyushengxin formula (QYSX), known as Kuijie formula, contains eight kinds of herbs.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, cancer-related inflammation has been clearly established as playing a critical role in promoting tumor progression and metastasis [9]. In fact, inflammatory processes have been evaluated using widely available biomarkers, including macrophage-stimulating protein, C-reactive protein, or other hematological parameters, such as the neutrophil-to-lymphocyte ratio (NLR) or platelet-tolymphocyte ratio (PLR) [10][11][12]. Among these inflammatory biomarkers, the preoperative blood NLR and PLR are negatively correlated with the prognosis of patients with solid tumors, including colorectal, pancreatic, non-small cell lung and ovarian tumors [13,14].…”
Section: Introductionmentioning
confidence: 99%